Media Modification Lactobacillus casei Strain Shirota with Skim Milk Enriched Green Coconut Water and Corn Starch - Sela Mustika Sari; Arista Wahyu Ningsih; Farida Anwari; Iif Hanifa Nurrosyidah (Universitas Airlangga, 2021)
Bacteria need a medium that can play an important role in their growth. One example of a medium is the medium De Mann Rogosa and Sharpe (MRS) which is a specific medium for the growth of lactic acid bacteria. The use of MRS media on an industrial scale is ineffective due to its relatively high price. The purpose of this study was to find out the effect of skim milk media enriched with green coconut water and cornstarch on the growth of Lactobacillus casei bacteria. The type of research conducted is experimental research with post test only control group design where there are two groups, namely the control group and the experimental group. The experimental group consisted of 3 types of samples, namely skim milk and green coconut water, skim milk and cornstarch, as well as skim milk and green coconut water and cornstarch. The comparison of treatment levels for each sample was 1:2 and 1:3 and analyzed, including bacterial growth curves, growth speed and bacterial generation time. From each concentration, the results found that the addition of green coconut water and cornstarch had a significant effect on the growth of Lactobacillus casei (P˂0.01) to the speed of growth and generation time. It was concluded that the higher the concentration added it can accelerate the growth of Lactobacillus casei.